Розробка рекомендаційної системи підбору лікарських засобів з використанням методів машинного навчання - Підгорний, М. О. (ХНУРЕ, 2024)
This work is devoted to the creation of a recommendation system for the selection of medicines based on machine learning methods. The system aims to personalize drug offers without using detailed patient medical records, instead analyzing publicly available drug datasets. The system provides recommendations based on prediction algorithms that take into account the complexity of drug selection and the specific needs of users.
Keywords: рекомендаційна система; підбір лікарських засобів; методи машинного навчання; персоналізовані рекомендації